2006
DOI: 10.1016/j.jvs.2006.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stent graft repair for infected thoracic aortic pseudoaneurysms—a durable option?

Abstract: Endovascular stent graft repair is effective and may be a durable option for infected pseudoaneurysms of the thoracic aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 17 publications
1
60
0
1
Order By: Relevance
“…In these patients, Vallejo and others reported that a combination (hybrid) of in situ reconstruction and EVT might be necessary. 190,228,[241][242][243][244][245][246][247][248] Subsequent explantation of EVT devices is especially challenging in patients with hybrid procedures and might not be technically feasible. Vallejo and colleagues 190 recommended EVT or hybrid procedures only in selected patients and concluded that open in situ repair remains the surgical management of choice.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…In these patients, Vallejo and others reported that a combination (hybrid) of in situ reconstruction and EVT might be necessary. 190,228,[241][242][243][244][245][246][247][248] Subsequent explantation of EVT devices is especially challenging in patients with hybrid procedures and might not be technically feasible. Vallejo and colleagues 190 recommended EVT or hybrid procedures only in selected patients and concluded that open in situ repair remains the surgical management of choice.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…After initial placement of the EVT device, explantation of the device and open surgical resection of the aortic MA and reconstruction may be considered in patients who can tolerate an open procedure. 189,227,228,[241][242][243][244][245][246][247][248] There are insufficient data to recommend EVT as the procedure of choice for patients with aortic MA (Figure 8 …”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The use of emergency stenting of iliac false aneurysm has been an effective treatment of ruptured iliac artery pseudo-aneurysm in our case. Ting et al 6 reported a successful endovascular stent repair of infected thoracic aortic pseudo-aneurysms under intravenous antibiotic cover followed by life-long oral antibiotics with a longterm follow-up (> 30 months) in three of their eight patients. Others have also reported a successful cover stent exclusion of external artery MRSA-infected pseudoaneurysm followed by 3 months of oral antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Though in cases of severe local inflammation, with or without haemorrhage, this technique can serve as bridging therapy. [60] Stent or stent-graft infections in the thoracic aorta are extremely rare. They are usually met in the literature as complications of systemic specific infections such as TBC or brucellosis.…”
Section: Infection Of Thoracic Aortamentioning
confidence: 99%